If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(1-2)+6g=12
We move all terms to the left:
2(1-2)+6g-(12)=0
determiningTheFunctionDomain 6g-12+2(1-2)=0
We add all the numbers together, and all the variables
6g-12+2(-1)=0
We add all the numbers together, and all the variables
6g-14=0
We move all terms containing g to the left, all other terms to the right
6g=14
g=14/6
g=2+1/3
| -124-4x=-15x+96 | | 11=9x+1 | | 12=-6x-24 | | (8.5)·(-3)=a | | x=x-17+73 | | -3-7c=7-7c | | -1/5m-9=-13 | | n/3+6=0 | | x-5(x-1)=x- | | 2/3-1/8x=1/6x-2/3 | | –0.5x+1.1=–2.9 | | (2)18=26+x | | 16+3n=48-5n | | 4x²+52=0 | | 2(6−2y)=−1(4y−9 | | 4x5=8x-11 | | 1x+1(2+2)=5 | | 16/10=q/5 | | x+18=x+26 | | 2m=-19.16 | | –6w+8=–2w | | 2k+8=20-2k | | -17+7x=31+4x | | -9f-5=-10f | | 3=-1/3(10)+b | | 260+20x=140 | | 32x+10=74 | | -2(1.7x+3.11)=4 | | -5x^2=-x+11 | | 5a-3=4a+10 | | 90=0.6x+18 | | 15=0+0x |